Traumatic dural venous sinus thrombosis; a challenge in management of head injury patients. (November 2018) - Afshari, Fardad T.; Yakoub, Kamal Makram; Zisakis, Athanasios; Thomas, Allan; Ughratdar, Ismail; Sturman, Steven; Belli, Antonio
Highlights: Traumatic dural venous sinus thrombosis complicates treatment of head injury patients. Decision to anti-coagulate traumatic venous sinus thrombosis is controversial. Anticoagulation decision is guided by interval repeat CT venograms and clinical picture. Anticoagulation guided by presence of thrombus propagation and other intracranial injuries. Abstract: Venous sinus thrombosis secondary to traumatic brain injury and head trauma is increasingly detected following contrast enhanced cranial imaging in acute trauma. The presence of sinus thrombosis poses further challenges in the management of traumatic brain injury patients with cerebral contusions, intraparenchymal haemorrhages or subdural/extradural haemorrhages. The decision to anti-coagulate such trauma induced venous sinus thrombosis is controversial and requires further attention and research to delineate risks versus benefits of treatment. In this article we report 4 cases of venous sinus thrombosis following head trauma and review the literature on management of such patients.